1992
DOI: 10.1002/jcp.1041500303
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the entry of reactive oxygen metabolites into target erythrocytes during neutrophil‐mediated antibody‐dependent cellular cytotoxicity

Abstract: Transmitted Soret band optical microscopy has been used to image the entry and passage of reactive oxygen metabolites across target erythrocytes. Due to the rapid cytosolic diffusion of hemoglobin in comparison to video rates, it was necessary to use erythrocytes with relatively immobilized hemoglobin. To achieve this, erythrocytes from patients with sickle cell anemia were used. The movement of reactive oxygen metabolites across rabbit IgG-opsonized sickle cells was observed in real time. These observations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Using Soret band microscopy and antibody-coated sickle cells as targets, we have recently shown that reactive oxygen metabolites can enter targets in an asymmetric (or unidirectional) fashion (Petty et al, 1992). As previously mentioned, the NAD(P)H-associated fluorescence is frequently found as aggregates near phagosomes.…”
Section: Discussionmentioning
confidence: 93%
“…Using Soret band microscopy and antibody-coated sickle cells as targets, we have recently shown that reactive oxygen metabolites can enter targets in an asymmetric (or unidirectional) fashion (Petty et al, 1992). As previously mentioned, the NAD(P)H-associated fluorescence is frequently found as aggregates near phagosomes.…”
Section: Discussionmentioning
confidence: 93%
“…2B). As time passes the erythrocytes disappear at this wavelength indicating cytosolic oxidation (data not shown; see Petty et al, 1992 for further kinetic Soret imaging studies). Since leakage of hemoglobin was not observed, the disappearance a t 430 nm is due to hemoglobin oxidation (Francis et al, 1988a).…”
Section: Cell Shapementioning
confidence: 89%
“…Unfortunately, their mechanism(s) of signal transduction are not understood completely. However, these various transduction mechanisms may all terminate in a calcium-and granule-dependent step required for the deposition of superoxide anions in targets, but not necessarily for the respiratory burst per se [Maher et al, 1993;Petty et al, 1992;Liang and Petty, 19921. In the present study our primary interest is in Fc receptor-triggered superoxide production. Neutrophils possess two classes of plasma membrane Fc receptors which are known as FcyRII (CD32) and FcyRIIIB (CD16).…”
mentioning
confidence: 99%